Prenatal depressive symptoms in Latinas: a qualitative investigation - Almeida, Isabel F. (Frontiers in Global Women's Health, 2024)
IntroductionExposure to prenatal depressive symptoms is associated with an increased risk of adverse pregnancy outcomes and child health complications. Research examining experiences of maternal depression among Latinas living in the United States, who have increased risk for experiencing prenatal depression symptoms, is lacking.ObjectivesThe purpose of this qualitative investigation is to examine the experience of prenatal depression symptoms among Latinas primarily of Mexican descent.MethodsFourteen pregnant Latinas shared their experiences of depressive symptoms during pregnancy in individual interviews and one focus group conducted in Spanish.ResultsThe most described symptoms of depression were periods of crying for no reason; feelings of irritability, sadness, and loneliness; and a loss of interest in normal activities. The participants coped with their depressive symptoms through distraction. Additionally, participants shared their beliefs that experiencing prenatal depressive symptoms was normal due to hormonal changes and that social support was protective. Themes about the baby “feeling” the mother's emotions during pregnancy and that prenatal depression is misunderstood also emerged.ConclusionsThese findings shed light on how Latina's experience maternal depressive symptoms and call for additional research on risk factors during the perinatal period among this growing subpopulation.